Kontekstual Budaya Melayu Riau dalam Pembelajaran Tari Cik Puan Sri Kampar di SMA Negeri 1 Tambang - Cornella Tiaradita (Ideas Publishing, 2023)
Students begin to lose their identity and encourage the entry of foreign cultures as well as a lack of understanding from the provision of dance material by cik puan sri kampar, SMA Negeri 1 Tambang is used as a writer to find out how deep the art of dance is by providing local dance material that is integrated into the curriculum. The aim of this research is to describe the contextualization of Riau Malay culture in learning the dance of cik puan sri kampar. This study uses a qualitative method. The results of the research are that the cik puan sri kampar dance is used as a means of communication, cultural values ​​in dance movements, implementation of the struggles of Kampar women and their meanings, as a reminder for the millennial generation to preserve local dances, integrated contextualization and curriculum.